A preliminary study of training effectiveness on i-Learn portal at Universiti Teknologi MARA (UiTM) / Mohd Nor Hajar Hasrol Jono . .. [et al.] - Hasrol Jono, Mohd Nor Hajar; Sardi, Janudin (Pm Dr.); Mat Zain, Nurul Hidayah; Abdul Aziz, Siti Rahayu; Abdul Aziz, Azlan (Penerbit UiTM (UiTM Press), 2009)
Effective training ensures that lecturers use the tools and test equipment, documentation, and spare parts efficiently to provide the required system operational reliability, through the proper installation, operation and maintenance of the prime mission equipment (IALA/AISM, 2001). i-Learn Center (i-LeC) was established on the 30th of December 2005 and operated under the Academic Affairs Division (HEA). The center is responsible for handling adaptation of e-learning in UiTM and providing two parts of training for UiTM lecturers across faculties and campuses throughout the country. The first part is i-Learn Portal System Training that deals with hands-on training of the system. The second part is e-Note Training that focuses on the optimization in using Microsoft Office (MS Word, MS Power Point and MS Excel) and Macromedia Flash MX in teaching environments. Questionnaires to gauge the effectiveness of the training were distributed to the lecturers in training and the data analyzed. Thus in this study, we present the findings and the results obtained reflecting the response of the lecturers about the effectiveness of i-Learn Portal System Training and e-Note Training. Finally, we also discuss on the direction of the findings in this study.